HUBUNGAN FAKTOR MANUSIA, ORGANISASI DAN TEKNOLOGI TERHADAP NET-BENEFIT DARI SIKP KABUPATEN DEMAK - Annisa' Arifatul Hikmah; Atik Mawarni; Dharminto Dharminto (Jurnal Kesehatan Masyarakat (Undip), 2021)
Sistem Informasi Kesehatan Puskesmas (SIKP) is a variation of the puskesmas management information system used by puskesmas in Demak Regency. SIKP began to be used to assist community health centers in managing patient services since 2016. However, in reality, there are still some obstacles in terms of human, organizational and technical factors. The purpose of this study was to determine the relationship between human, organizational and technological factors (HOT-Fit) with the Net-Benefit of using SIKP at Dempet Health Center and Gajah 2 Health Center, Demak Regency. This research is a quantitative research using explanatory research method and cross sectional study design. The total population of SIKP users are 43 officer respondents, with details of 4 Registration officers, 9 BP-UMUM officers, 28 KIA officers, 4 Pharmacy officers. The results showed that most respondents were users of information systems aged 31-40 years (44%), and had a work period of more than 15 years (39.5%). The results of the correlation test showed that there was a weak positive relationship between human factors and the net-benefit of SIKP (p-value = 0.021, r = 0.351), but there is no relationship between the other 2 variables, between organizational factors and Net-benefit (p value = 0.392, r = 0.194) and between technology factors and Net-benefit (p value = 0.994, r = 0.001). It is recommended that monitoring and evaluation of routine use from both the Puskesmas and the Health Office are recommended so that it can add to the positive net-benefits of SIKP.